Explosive power in gymnasts: is there any scientific basis for gender differences? - Aleksic-Veljkovic, A.; Velickovic, S.; Sands, W. A.; Durovic, D.; Trajkovic, N. (Facta Universitatis: Series Physical Education and Sport, 2016)
The purpose of this study was to examine potential differences in vertical jump performance between male and female highly trained gymnasts, and to determine the relationship between parameters of the vertical jump performance and skill difficulty on the floor exercise. Forty-six highly trained gymnasts, comprising 15 female (Mean±SD; age: 21.08±1.83 y, height: 159.37±4.87 cm, mass: 50.88±5.41 kg) and 33 male (Mean±SD; age: 21.5±1.79 years, height: 170.67±4.66 cm, mass: 67.08±6.26 kg) consented to participate in study. Results showed statistically significant differences between male and female gymnasts (P < 0.001) in jump height and relative and peak power, while no statistically significant differences (P > 0.05) were shown between instantaneous powers. Correlation coefficients for CMJ variables were calculated for both groups. Statistically significant positive correlations were found only between D score values and jump height in male gymnasts (0.53) and relative jump power (0.39). Among female gymnasts, statistically significant, but negative correlations between E scores and jump height (-0.64) and with relative power (- 0.65), and between F scores and jump height (-0.52) were found.